2021
DOI: 10.1038/s41396-020-00875-w
|View full text |Cite
|
Sign up to set email alerts
|

The amphibian microbiome exhibits poor resilience following pathogen-induced disturbance

Abstract: Infectious pathogens can disrupt the microbiome in addition to directly affecting the host. Impacts of disease may be dependent on the ability of the microbiome to recover from such disturbance, yet remarkably little is known about microbiome recovery after disease, particularly in nonhuman animals. We assessed the resilience of the amphibian skin microbial community after disturbance by the pathogen, Batrachochytrium dendrobatidis (Bd). Skin microbial communities of laboratory-reared mountain yellow-legged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 72 publications
2
47
0
Order By: Relevance
“…Raw paired fastq reads were processed to generate amplicon sequence variants (ASVs) [ 53 , 54 ]. In brief, raw sequences were filtered, trimmed, and merged using the dada2 R package, triplicate technical replicates were merged bioinformatically after confirmation of replicability, and OTUs were defined as unique “amplicon sequence variants” by dada2 [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Raw paired fastq reads were processed to generate amplicon sequence variants (ASVs) [ 53 , 54 ]. In brief, raw sequences were filtered, trimmed, and merged using the dada2 R package, triplicate technical replicates were merged bioinformatically after confirmation of replicability, and OTUs were defined as unique “amplicon sequence variants” by dada2 [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, there was limited opportunity for introduction of new microbes to each individual amphibians' skin. This may have reduced detectable effects on the skin microbiota after exposure to Bd, especially compared to what has been observed in previous work in non-sterile environments (Jani et al, 2021) because there was no reservoir of microbes from which new members could be recruited.…”
Section: Changes In the Microbial Community In Response To Bd Exposur...mentioning
confidence: 84%
“…Previous studies report that skin‐associated microbial communities change after Bd infection (Jani & Briggs, 2014, 2018; Jani et al, 2017, 2021). While we did not observe shifts in any community traits (Figure 4), our PERMANOVA analysis revealed that Bd infection was associated with a significant difference in community composition between infected and noninfected individuals (Figure ).…”
Section: Discussionmentioning
confidence: 97%
“…Adaptive management frameworks for amphibians that are threatened by Bd include interventions to prevent further extinctions [17,18]. For instance, efforts have focused on reducing Bd in the environment [19] and infections on the amphibian hosts [20,21], while also improving the capacity of populations to persist despite increased disease-related mortality [18]. In areas where Bd is enzootic, additional pressures, such as climate change and habitat degradation, can compromise already struggling populations [17].…”
Section: Introductionmentioning
confidence: 99%